The influence of share buybacks on ill-health and health inequity: an exploratory analysis using a socio-ecological determinants of health lens - Benjamin Wood; Gary Sacks (Globalization and Health, 2023)
Abstract Introduction Share buybacks, when a corporation buys back its own shares, are recognised as having potentially harmful impacts on society. This includes by contributing to economic inequalities, and by impeding investments with the potential to protect and promote the welfare of various stakeholders. Share buybacks, however, have received minimal analytical attention in the public health literature. This paper aimed to explore the potential influence of share buybacks on population health and health inequity using a socio-ecological determinants of health lens. Methods We conducted a descriptive analysis of share buybacks made by corporations listed on United States (US) stock exchanges between 1982 and 2021, using quantitative data sourced from Compustat. We examined annual trends in share buyback expenditure, including comparisons to dividend, net income, capital expenditure, and research and development expenditure data. We then purposively sampled a set of corporations to provide illustrative examples of how share buybacks potentially influence key socio-ecological determinants of health. The examples were: i) three COVID-19 vaccine manufacturers; ii) five of the world’s largest fossil fuel corporations; and iii) US car manufacturer General Motors. For these, we conducted an analysis of data from Compustat, company reports and grey literature materials, focusing on key sources of profits and their allocation to share buybacks and particular investments. Results US-listed corporations spent an estimated US$9.2 trillion in real terms on share buybacks between 2012 and 2021 (nearly 12 times more than from 1982 to 1991). The contribution of share buybacks to total shareholder ‘returns’ increased from 11% in 1982 to 55% in 2021, with expenditure on shareholder returns increasing considerably relative to capital, research and development expenditure over this period. The three examples illustrated how some corporations have prioritised the short-term financial interests of their shareholders, including via implementing large share buyback programs, over investments with considerable potential to protect and promote the public’s health. Conclusion The potentially substantial impacts of share buybacks on health warrant increased research and policy attention. Arguably, more must be done to regulate share buybacks as part of efforts to address the corporate drivers of ill-health and inequity.